KAJIAN KESEJAHTERAAN SAPI PADA BEBERAPA PETERNAKAN DI KOTA PANGKALPINANG - Nurhayati Nurhayati; Nur Annis Hidayati; Budi Afriyansyah (EKOTONIA: Jurnal Penelitian Biologi, Botani, Zoologi, dan Mikrobiologi, 2017)
Animal welfare is importan to improve life quality of animal in husbandry. Statistically, Pangkalpinang has the highest number of cow husbandry among other cities in Bangka. This study aimed to asses the animal welfare on several cow husbandries in Pangkalpinang. The assesment was held on September 2015 on 6 husbandries in Pangkalpinang. Interview, observation and Animal Needs Index (ANI) to collect data. Based on ANI method, there are 5 categories of animal welfare, wich are movement, social contact, quality flooring, light and air, and cleanlines cowshed. Study showed that in general, cattle cow in welfare candition (ANI score 23,8)